Case study of a voluntary aviation safety and environmental accreditation programme. (July 2017) - Oldham, Kevin; Stanton, Jack; Bilderbeck, Matt; Spinetto, Jessica
Highlights: High quality official data can be used to explore safety performance relationships. Participation in robust aviation accreditation programme associated with fewer events. Independently accredited voluntary programmes may be associated with safer operation. Participation in such programmes may convey information on future safety performance. Abstract: Adopting the principle that it is better to self-regulate than to be regulated; voluntary accreditation schemes have been introduced by a range of high-hazard industries to lift safety and environmental performance. Both industries and regulators need to know if such programmes are effective. This paper presents a comparative case study of safety and environmental performance for a voluntary industry-led accreditation programme (Aircare) in the New Zealand agricultural aviation sector. The study hypotheses relate to rates of reported: Accidents Incursions and other incidents Discharge and low flying occurrences Equipment defects While there were observed differences in rates for the above occurrence types between accredited, transitional and non-accredited operators, none of these was found to be statistically significant, therefore the null hypotheses could not be rejected. An additional sensitivity test was undertaken in which all examined occurrences were combined into one variable "all events". Non-accredited operators had a higher rate of these combined occurrences (risk ratio 1.32) and this finding was significant at a 90%, one-tailed, level of confidence. The additional test suggests that statistically significant results may emerge as more data becomes available. This finding indicates that participation in robust voluntary safety and environmental programmes may be associated with lead indicators of safer operations and fewer environmental incidents. Participation in such programmes may therefore convey important information on likely future safety and environmental performance.